ANALISIS KINERJA KARYAWAN KOPERASI KREDIT BANURI HARAPAN KITA DI BATANG TARANG KABUPATEN SANGGAU - Alisaputri, Nurania; Khosmas, F.Y.; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This thesis entitled "Performance Analysis of Employees of Credit Union (CU) Banuri Harapan Kita in Batang Tarang of Sanggau District". The general problem of this research is "How is the performance of Employees Credit Union (CU) Banuri Harapan Kita in Batang Tarang whit the focus of research is team work, discipline, skill, and quality of work and data source of this research is seven employees, General Manager and document. The research used descriptive method with qualitative approach. The data collection tools include observation guidelines, interview guides and notes. The result of this study indicates; 1) Excellent employees’ team work are shown by the communication that exists between employees and superiors and always support and assist in completing the work. 2) Employees discipline are good enough with the awareness of employees who know rules that applied regarding break-in and return times and employees do not infringe and attendance list either. 3). Employees already have the skills in completing the tasks contained in the Job Descriptions of each department. 4). the quality of work employees in good working, if in the employees make mistakes, it will be corrected immediately in order to maintain the quality of the institution. Keywors: Employees’ Performance, Credit Union